Common milkweed (Asclepias syriaca L.) response to sulcotrione - Gajić Umiljendić, Jelena; Sarić-Krsmanović, Marija; Šantrić, Ljiljana; Radivojević, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
A laboratory bioassay was conducted to investigate common milkweed response to sulcotrione. Sulcotrione was applied in concentration series of 0.15-0.90 kg a.i./ha without a surfactant and with Dash® at 1 L/ha. Plants grew for 14 days, upon which period morphological (height and fresh weight) and physiological parameters (content of carotenoids, chlorophyll a and chlorophyll b) were measured. Visual crop injury was estimated 7 and 14 days after treatment. Sulcotrione caused leaf bleaching and reduction in pigments content in common milkweed leaves and the degree of change depended on application rates and whether it was applied with or without the surfactant. Inhibition was slightly higher in plants which were treated with a combination of herbicide and surfactant. Based on the findings in this study, common milkweed showed moderate susceptibility to the recommended field rates of sulcotrione.